COMMUNITY-BASED LIFELONG LEARNING IN MAJELIS TAKLIM TO SUPPORT THE ACHIEVEMENT OF SUSTAINABLE DEVELOPMENT GOAL 4 (SDG 4) - Siti Saodah Susanti; Hery Saparudin; Azizudin Mustopa (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze and develop a conceptual model of community-based lifelong learning practices in Majelis Taklim to support the acceleration of Sustainable Development Goal 4 (SDG 4). The study employed a qualitative meta-synthesis approach combined with extensive content analysis of empirical findings from previous studies, complemented by policy documents on non-formal Islamic education. The findings reveal that Majelis Taklim has evolved into an inclusive, adaptive, and sustainable community learning center. This transformation is supported by a conceptual model integrating four key components: participatory leadership, dialogic learning grounded in participants' lived experiences, the development of contextualized learning materials, and reflective evaluation oriented toward socio-religious empowerment. The study highlights the importance of formal policy recognition and strategic government partnerships in strengthening the role of Majelis Taklim. As locally rooted faith-based institutions, Majelis Taklim possess substantial institutional capacity to serve as key catalysts for advancing the United Nations' global education agenda by promoting lifelong learning opportunities within local communities.